Metode Parenting Prophetic dalam Membangun Akhlak Mulia - Rizky Putri Amalia (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2019)
Morals are a reflection of attitudes in a person that have an important influence on various aspects of life, this is the reason why the cultivation of noble character must be carried out from an early age. Prophetic parenting is considered the right method for mothers in the Al-Ihsan taklim assembly who act as madrasatul ula, to instill noble character in their children from an early age. This study aims to find out how the process of implementing prophetic parenting is to build noble character in the Al-Ihsan taklim assembly. The results showed that the process of implementing prophetic parenting carried out by mothers at the Al-Ihsan taklim assembly was to apply it to simple things, such as giving instructions and directions, providing good education, especially in understanding obedience to Allah SWT and his parents based on the character of the prophet Muhammad SAW as early as possible.